Analysis Of Internal Control Of The Cash Management System In Medan Mayor’s Office - Yunisa, Widya; Harahap , Rahmat Daim (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to analyze the internal control implemented in the cash management system at the Medan Mayor’s Office. Internal control is a series of actions implemented within an organization to protect assets, ensure the accuracy and reliability of financial information, and promote operational effectiveness and efficiency. In the context of cash management at the Medan Mayor’s Office, internal control has an important role in maintaining the integrity and reliability of the cash management process in a timely and accurate manner. The problems identified in this study include several aspects related to internal control in the cash management system. First, aspects of inadequate segregation of duties and responsibilities can result in potential errors and abuse. Second, unclear and nonstandardized policies and procedures can hinder the efficiency and transparency of cash management. Third, the lack of effective oversight and monitoring can increase the risk of inaccuracies and cash losses. Fourth, information systems that are not well integrated can hinder the accessibility and reliability of financial data.